National Reunification and Educational Reforms in Vietnam from 1975 to 1985 - Van Kim, Nguyen (VNU Journal of Science: Policy and Management Studies, 2024)
After April 30, 1975, Vietnam became an independent and unified nation. Along with the policies of quickly achieving statehood unification, establishing a national government structure, and fostering consensus and harmony between the two regions of North and South,... various economic, social, educational, and cultural issues are also of particular concern to the Party and the State of Vietnam. Recognizing the role and mission of education in the nation's development, considering education and training, science and technology as the top national policies, Vietnam's education system has early on aimed at promoting the beautiful values of national culture, continuously raising public awareness, nurturing character, and training talented individuals. Education plays a central role in a knowledge-based economy's development, building a learning society, the desire to contribute, fostering a growth mindset, and progressively integrating Vietnam into the world.Through the exploitation of diverse information sources, the article attempts to present and analyze the context and current state of Viet Nam education after 1975; the policies, implemented solutions, and the fundamental achievements of Vietnamese education in the first decade of the unified era.